Greenham Barton Manor
The manor house built in a time of civil war, has lost its original stone or thatched roof. Its extended plan also centers about the hall. This was the great common room of the household for eating and sleeping purposes. The Lord of the Manor and his Lady had a private apartment for themselves, which in this example also has access to a tower for defense. The entrance with a small room above, is also defensive in character. It leads to a passage between the kitchens and the hall from which it is separated by a timber wall, or screen. Houses such as this reflected the new unity of common purpose which survival from the plague had given. Norman French and Anglo-Saxon had merged into a common tongue, and while the King and the Church preoccupied themselves with supremacy, the English Gentleman, Lord of the manor, emerged, supported by free men who shared the house, and were no longer serfs.